Business letters the easy way - Geffner, Andrea B. (Barron’s, 1991)
This newly updated edition shows how to write business letters that are clear, concise, interesting, grammatical and productive. Sample letters apply to sales, public relations, job-hunting, claims and adjustments, business-to-business correspondence, and much more.